PENERAPAN METODE TAHLILI DALAM SYARAH HADIS - Juriono Juriono (Al-Mu'tabar, 2022)
ABSTRACT The Qur'an has received descriptions and explanations through the science of interpretation to be able to understand it properly. Likewise, the Hadith needs a method to understand it in order to avoid misunderstandings. The terms Fiqhul Hadith and Syarhul Hadith then emerged in an effort to understand the hadiths of the Prophet Muhammad. among scholars. But most ordinary people can not distinguish between the two. This paper will briefly examine the differences between Fiqhul Hadith and Syarhul Hadith, then try to apply one of the methods in the syarah of Hadith, namely tahlili. By providing understanding and examples in application, it is hoped that it will provide a good understanding regarding the syarah of hadith. ABSTRAK Alquran telah mendapatkan uraian dan penjelasan melalui ilmu tafsir untuk dapat memahaminya dengan baik. Demikian pula halnya Hadis yang perlu metode dalam memahaminya agar terhindar dari kesalahpahaman. Istilah Fiqhul Hadis dan Syarhul Hadis kemudian muncul dalam upaya memahami hadis-hadis Nabi Saw. di kalangan ulama. Namun kebanyakan masyarakat awam belum dapat membedakan antara keduanya. Tulisan ini akan sedikit mengupas perbedaan antara Fiqhul Hadis dan Syarhul Hadis, selanjutnya mencoba menerapkan salah satu metode dalam syarah Hadis yaitu tahlili. Dengan memberikan pengertian dan contoh dalam penerapan diharapkan dapat memberikan pemahaman yang baik terkait syarah hadis.